Model Based Identification of Linezolid Exposure–toxicity Thresholds in Hospitalized Patients - Fang, Jie; Zhang, Xiao-Shan; Zhang, Chun-Hong; Zhou, Zi-Ye; Han, Lu; Wang, Ye-Xuan; He, Xiao-Shuang; Bian, Xiao-Lan; Lin, Guan-Yang; Jiao, Zheng; Dai, Ying; Yu, Xu-Ben; et al. (Frontiers in Pharmacology, 2021)
Evidence supports linezolid therapeutic drug monitoring as the exposure-response relationship has been identified for toxicity among patients receiving linezolid, but the data to establish the upper limit are limited and the published toxicity thresholds range widely. The purpose of this study was to determine the linezolid exposure-toxicity thresholds to improve safety of linezolid. This is a multicenter retrospective study of adult patients treated with linezolid from 2018 to 2019. The population pharmacokinetic model of linezolid was established based on 270 plasma concentrations in 152 patients, which showed creatinine clearance and white cell count are covariates affecting the clearance of linezolid, and serum albumin is the covariate affecting the volume of distribution. Classification and regression tree analysis was used to determine the linezolid the exposure thresholds associated with an increased probability of toxicity. Among 141 patients included for toxicity analysis, the rate of occurring toxicity was significantly higher among patients with AUC0-24, d1 ≥163 mg·h/L, AUC0-24, d2 ≥207 mg·h/L, AUC0-24, ss ≥210 mg·h/L, and Cmin,d2 ≥6.9 mg/L, Cmin,ss ≥6.9 mg/L, while no threshold was discovered for Cmin, d1. Those exposure thresholds and duration of linezolid treatment were independently associated with linezolid-related toxicity in the logistic regression analyses. In addition, the predictive performance of the AUC0-24 and Cmin thresholds at day 2 and steady state were close. Considering that the AUC estimation is cumbersome, Cmin threshold at 48-h and steady state with value of ≥ 6.9 mg/L is recommended to improve safety, especially for patients with renal insufficiency and patients with low serum albumin.